Travel with the Wild Wind. (2nd July 2020) - Xue, Yiwei; Wei, Miao
Abstract : Xue Yiwei is a contemporary Chinese writer based in Montreal, Canada. Xue's writing is stylistically elegant, linguistically beautiful, but at times intellectually challenging. Influenced by French existentialism, Xue has a dazzling talent for revealing the absurdity and emptiness of history in his works. In this early short story, first published in 1999, the first-person narrator accidently finds out the secret of her late husband just before his funeral, which makes her disillusioned about her marriage. This story was collected in The Dolphin That Doesn't Want to Leave ( Buken liqu de haitun ) as "Yu kuangfeng yiqi lüxing" by the Shanghai Literature and Art Publishing House in 2012.